HUBUNGAN KADAR KADMIUM DALAM DARAH DENGAN KADAR SGOT PADA PEKERJA BENGKEL LAS DI SURAKARTA - Ramadhan, Putri Wahyu; Lestari, Mastuti Widi (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2023)
Welding workshop workers have the potential to be exposed to heavy metal Cd vapors. Cd metal vapor is a solid particle originating from the cathode wire in the welding industry. Cd that enters the human body will be absorbed and bound to metallothionein (Cd-MT) and accumulates in the liver. Chronic exposure to Cd causes accumulation of Cd in the liver. Compounds containing poisons that are quite high, some of them will attack proteins, causing liver cells to break and be damaged and release SGOT enzymes which eventually enter the blood and SGOT levels increase. Increased levels of SGOT indicate the possibility of damage to cells in the liver. The purpose of this study was to find out whether there is a potential for damage to liver cells due to Cd exposure as seen from the increased levels of SGOT in welding workshop workers in Laweyan, Surakarta. This type of research is observational analytic with a cross sectional approach using a purposive sampling technique. The results of statistical analysis using the non-parametric Spearman rank test from the correlation test, the significance value of 30 samples is 0.920, so p>0.05, the Correlation coefficient value is -0.019 indicating that there is no relationship between Cd levels and SGOT levels in the blood of welding workshop workers in Laweyan Surakarta weakly correlated.